Pengaruh Kualitas Pelayanan Dan Pengetahuan Masyarakat Terhadap Minat Menabung Pada Bank Syariah Di Kecamatan Muara Siau Kabupaten Merangin - Nofia Ramadanti; Novi Mubyarto; Nurrahma Sari Putri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This study is about the influence of service quality and public knowledge on interest in saving at Sharia Banks in Muara Siau District, Merangin Regency. The purpose of this study is to determine whether there is a significant influence between service quality and public knowledge on interest in saving at Sharia Banks in Muara Siau District, Merangin Regency. The type of this research is quantitative with data collection techniques in this study namely the distribution of questionnaire instruments, observation, interviews and documentation, while for data analysis the researcher used multiple linear regression analysis by conducting partial tests, simultaneous tests and determination tests. The results of the study explain the influence of public service quality on interest in saving at Sharia Banks in Muara Siau District, Merangin Regency, namely based on the value of the financial knowledge variable (X1) which has a t count of 2.145. Then for t table = 1662, obtained t count > t table, namely 2.145 > 1.662. Therefore, there is a significant influence between the quality of public service on interest in saving at Sharia Banks in Muara Siau District, Merangin Regency. The knowledge variable influences the interest in saving, this is based on the value of the community knowledge variable (X2) which has a t-count value of 3.241, so t-count> t-table, namely 3.241> 1.662, so there is a significant influence between community knowledge on the interest in saving at Islamic Banks in Muara Siau District, Merangin Regency. The joint influence of service quality and knowledge on the interest in saving at Islamic Banks in Muara Siau District, Merangin Regency, is known simultaneously based on the calculated F value, namely 14.323> 2.707 and the significance value is less than 0.05, namely 0.000 <0.05. So that the variables of service quality and community knowledge together have a significant influence on the interest in saving at Indonesian Islamic Banks in Muara Siau District, Merangin Regency.